INTEGRASI METODE LEAN MANUFACTURING - SPC - ERGONOMI GUNA MEMINIMALISIR PEMBOROSAN PROSES PRODUKSI AIR MINUM DALAM KEMASAN DI PT DCDC - Muh Qorik Maulana Asim Aldifa; Nina Aini Mahbubah; Purwanto Purwanto (Fakultas Teknik, Universitas Riau Kepulauan, 2026)
Efficiency is essential in production. PT. DCDC encounters challenges such as defects, non-ergonomic work motions, excess inventory, and low safety compliance. This study aims to reduce waste in the production of bottled mineral water by integrating lean manufacturing, statistical process control (SPC), and ergonomic practices. Data were gathered through direct observation and historical records, with analyses including control charts, process mapping, and root cause analysis. The findings indicate a total cycle time of 5,044.45 seconds, with only 4% allocated to value-added activities. Proposed improvements include using SPC to minimize defects, applying the 5S principles, enhancing ergonomics in material handling, and promoting a more vigorous health and safety culture.